Colombia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
In this paper, the structure of Colombia's financial sector is analyzed and various risks of the financial sector are studied. Supervision of the financial system can be performed by supervisory architecture, banking supervision, various securities, and insurance policies. Systemic liquidity provision, deposit insurance, and bank resolution form the financial safety net. Finally, financial stability and macroprudential framework have been discussed. Macroprudential tools and policies are also explained in detail.